"Evaluation of OFDM-IDMA & OFDMA scheme in optical domain" - Tripathi, Abhishek; Sriwas, S. K.; Singh, R. K. (International Journal of Engineering and Technology, 2018)
In this paper we proposed the system model for O-OFDM-IDMA and O-OFDMA in VLC Channel (Visible Light Communication as a media) and compared their performances in terms of receivers decoding complexities, BER (Bit Error Rate) and PAPR (Peak to average power ratio). For asymmetric clipping at zero both the multicarrier transmission schemes are tailored after OFDM modulation. The result of simulation shows that O-OFDM-IDMA is very power efficient in comparison to O-OFDMA for higher throughput values for the exceeding threshold value at a cost of higher decoding and computational complexity involved. The PAPR variation is not much significant for O-OFDM-IDMA and O-OFDMA. These results can be used as a basis for designing future Visible Light Communication based networks.